Are coping styles consistent in the teleost fish Sparus aurata through sexual maturation and sex reversal? - Castanheira, Maria Filipa (2017)
Individual differences in behaviour and physiological responses to stress are associated with evolutionary adaptive variation and thus raw material for evolution. In farmed animals, the interest in consistent trait associations, i.e. coping styles, has increased dramatically over the last years. However, one of limitations of the available knowledge, regarding the temporal consistency, is that it refers always to short-term consistency (usually few weeks). The present study used an escape response during a net restraining test, previously shown to be an indicative of coping styles in seabream, to investigate long-term consistency of coping styles both over time and during different life history stages. Results showed both short-term (14 days) consistency and long-term (8 months) consistency of escape response. However, we did not found consistency in the same behaviour after sexual maturation when the restraining test was repeated 16, 22 and 23 months after the first test was performed. In conclusion, this study showed consistent behaviour traits in seabream when juveniles, and a loss of this behavioural traits when adults. Therefore, these results underline that adding a life story approach to data interpretation as an essential step forward towards coping styles foreground. Furthermore, a fine-tuning of aquaculture rearing strategies to adapt to different coping strategies may need to be adjusted differently at early stages of development and adults to improve the welfare of farmed fish.